Photophysics and photochemistry of NIR absorbers derived from cyanines: key to new technologies based on chemistry 4.0 - Strehmel, Bernd; Schmitz, Christian; Kütahya, Ceren; Pang, Yulian; Drewitz, Anke; Mustroph, Heinz (Beilstein Journal of Organic Chemistry, 2020)
Cyanines derived from heptamethines were mainly discussed regarding their functionalization to broaden the solubility in different surroundings exhibiting either hydrophilic or hydrophobic properties and to tailor made the ΔGet photopysical properties with respect to absorption and fluorescence. Electrochemical properties were additionally considered for some selected examples. The cyanines chosen comprised as end groups either indolenine, benzo[e]- or benzo[cd]indolium pattern, which facilitated to shift the absorption between 750–1000 nm. This enabled their use in applications with light sources emitting in the near-infrared (NIR) region selected from high power LEDs or lasers with line-shaped focus. The absorbers considered were discussed regarding their function as sensitizer for applications related to Chemistry 4.0 standards. These were mainly photopolymer coatings, which can be found for applications in the graphic industry or to protect selected substrates. The huge release of heat on demand upon turning ON or OFF the NIR light source enables them for photothermal treatment in processes requesting heat to initiate either chemical (activated reactions) or physical (melting, evaporation) events.
Keywords: chemistry 4.0; cyanine; near infrared; photopolymer; polymer synthesis; sensitizer

Ullmann's Encyclopedia of Industrial Chemistry - Mustroph, H. (Dyes, General Survey, 2014)

The Cyanine Dyes and Related Compounds - Hamer, F. E. (Interscience Publishers, John Wiley & Sons, 1964)

(untitled) - Fabian, J.; Nakazumi, H.; Matsuoka, M. (Chem. Rev., 1992)

Chemistry of Heterocyclic Compounds - Sturmer, D. M. (Syntheses and Properties of Cyanine and Related Dyes, 1977)

(untitled) - Schmitz, C.; Halbhuber, A.; Keil, D.; Strehmel, B. (Prog. Org. Coat., 2016)

(untitled) - Kocaarslan, A.; Kütahya, C.; Keil, D.; Yagci, Y.; Strehmel, B. (ChemPhotoChem, 2019)

(untitled) - James, N. S.; Chen, Y.; Joshi, P.; Ohulchanskyy, T. Y.; Ethirajan, M.; Henary, M.; Strekowski, L.; Pandey, R. K. (Theranostics, 2013)

(untitled) - Choi, H. S.; Nasr, K.; Alyabyev, S.; Feith, D.; Lee, J. H.; Kim, S. H.; Ashitate, Y.; Hyun, H.; Patonay, G.; Strekowski, L.; Henary, M.; Frangioni, J. V. (Angew. Chem., Int. Ed., 2011)

(untitled) - Lipowska, M.; Patonay, G.; Strekowski, L. (Synth. Commun., 1993)

(untitled) - Vollmann, H. W. (Angew. Chem., 1980)

Ullmann's Encyclopedia of Industrial Chemistry - Baumann, H.; Hoffmann-Walbeck, T.; Wenning, W.; Lehmann, H.-J.; Simpson, C. D.; Mustroph, H.; Stebani, U.; Telser, T.; Weichmann, A.; Studenroth, R. (Imaging Technology, 3. Imaging in Graphic Arts, 2015)

(untitled) - Baumann, H. (Chem. Unserer Zeit, 2015)

(untitled) - Strehmel, B.; Ernst, S.; Reiner, K.; Keil, D.; Lindauer, H.; Baumann, H. (Z. Phys. Chem., 2014)

(untitled) - Brömme, T.; Schmitz, C.; Oprych, D.; Wenda, A.; Strehmel, V.; Grabolle, M.; Resch-Genger, U.; Ernst, S.; Reiner, K.; Keil, D.; Lüs, P.; Baumann, H.; et al. (Chem. Eng. Technol., 2016)

(untitled) - Strehmel, B.; Schmitz, C.; Bromme, T.; Halbhuber, A.; Oprych, D.; Gutmann, J. S. (J. Photopolym. Sci. Technol., 2016)

(untitled) - Schmitz, C.; Strehmel, B. (ChemPhotoChem, 2017)

(untitled) - Schmitz, C.; Gökce, B.; Jakobi, J.; Barcikowski, S.; Strehmel, B. (ChemistrySelect, 2016)

(untitled) - Pitz, H. (Vorrichtung und Verfahren zur Zuführung von Strahlungsenergie auf einen Bedruckstoff in einer Flachdruckmaschine, 2003)

(untitled) - Schlörholz, M.; Keil, D.; Pitz, H. (Verfahren zum Trocknen von Druckfarbe auf einem Bedruckstoff, 2008)

(untitled) - Ernst, S.; Peiter, G. D.; Pitz, H.; Reiner, K.; Mistol, J.; Schlörholz, M. (IR dyes and laser markable articles comprising such IR dyes, 2007)

(untitled) - Nakhaei, M. R.; Mostafa Arab, N. B.; Kordestani, F. (Adv. Mater. Res., 2012)

(untitled) - Brunnecker, F.; Sieben, M. (Laser Tech. J., 2010)

(untitled) - Wissemborski, R.; Klein, R. (Laser Tech. J., 2010)

(untitled) - Jones, I. A.; Taylor, N. S.; Sallvanti, R.; Griffith, J. (Int. J. Res. Eng. Technol., 2014)

(untitled) - Ernst, S.; Keil, D.; Reiner, K.; Senns, B. (NIR-Absorber Additive für das Laserstrahlschweißen von Kunststoffen, 2018)

(untitled) - Pérez-Barrado, E.; Darton, R. J.; Guhl, D. (MRS Commun., 2018)

(untitled) - Patel, C.; Patel, A. J.; Patel, R. C. (Int. J. Sci. Res. Dev., 2017)

(untitled) - Loccufier, J. (Developing Agent Precursor for Laser Markable Composiitons, 2018)

(untitled) - Waumans, B.; Geuens, I.; Callant, P.; Van Aert, H. (Security documents and colour laser marking methods for securing them, 2015)

(untitled) - Thaker, J. (Laser fusible coating compositions used for laser marking systems and methods, 2011)

(untitled) - Koenemann, M.; Boehm, A.; Pschirer, N. G.; Qu, J.; Mattern, G. (Substituierte Rylenderivate, 2007)

The Theory of the Photographic Process - Brooker, L. G. S. (Sensitizing and Desensitizing Dyes, 1966)

The Theory of the Photographic Process - Sturmer, D. M.; Heseltine, D. W. (Sensitizing and Desensitizing Dyes, 1977)

Ullmann's Encyclopedia of Industrial Chemistry - Keller, K.; Kampfer, H.; Matejec, R.; Lapp, O.; Krafft, W.; Frenken, H.; Lührig, H.; Scheerer, R.; Heilmann, M.; Meckl, H.; Bergthaller, P.; Hübner, D.; et al. (Photography, 2000)

The Chemistry of Synthetic Dyes - Ficken, G. E. (Cyanine Dyes, 1971)

Methoden der organischen Chemie - Berlin, L.; Riester, O. (Methoden zur Herstellung von Cyaninen (Polymethinen), 1972)

The Chemistry of Heterocyclic Compounds - Sturmer, D. M. (Syntheses and Properties of Cyanine and Related Dyes, 1977)

Kirk-Othmer Encyclopedia of Chemical Technology - Sturmer, D. M. (Cyanine Dyes, 1979)

Ullmanns Enzyklopädie der Technischen Chemie - Raue, R.; Riester, O. (Methinfarbstoffe, 1979)

(untitled) - Mishra, A.; Behera, R. K.; Behera, P. K.; Mishra, B. K.; Behera, G. B. (Chem. Rev., 2000)

(untitled) - Steiger, R.; Hediger, H.; Junod, P. (Photogr. Sci. Eng., 1980)

(untitled) - Beretta, P.; Jaboli, A. (Photogr. Sci. Eng., 1974)

(untitled) - Herz, A. H. (Photogr. Sci. Eng., 1974)

(untitled) - Herz, A. H. (Photogr. Sci. Eng., 1974)

(untitled) - Norland, K.; Ames, A.; Taylor, T. (Photogr. Sci. Eng., 1970)

(untitled) - McRae, E. G. (Aust. J. Chem., 1961)

(untitled) - Kasha, M.; Rawls, H. R.; Ashraf El-Bayoumi, M. (Pure Appl. Chem., 1965)

(untitled) - McRae, E. G.; Kasha, M. (J. Chem. Phys., 1958)

(untitled) - Hestand, N. J.; Spano, F. C. (Chem. Rev., 2018)

(untitled) - Scheibe, G. (Angew. Chem., 1937)

(untitled) - Jelley, E. E. (Nature, 1937)

(untitled) - Dewar, M. J. S. (J. Chem. Soc., 1950)

(untitled) - Knott, E. B. (J. Chem. Soc., 1951)

Dyes and Chromophores in Polymer Science - Strehmel, B.; Brömme, T.; Schmitz, C.; Reiner, K.; Ernst, S.; Keil, D. (NIR-Dyes for Photopolymers and Laser Drying in the Graphic Industry, 2015)

(untitled) - Yuan, Z.; Lee, S.-L.; Chen, L.; Li, C.; Mali, K. S.; De Feyter, S.; Müllen, K. (Chem. – Eur. J., 2013)

Near-Infrared Organic Materials and Emerging Applications - Wang, Z. Y. (CRC Press, 2013)

(untitled) - Schmitz, C.; Strehmel, B. (J. Coat. Technol. Res., 2019)

(untitled) - Lee, H.; Berezin, M. Y.; Henary, M.; Strekowski, L.; Achilefu, S. (J. Photochem. Photobiol., A, 2008)

(untitled) - Benson, R. C.; Kues, H. A. (J. Chem. Eng. Data, 1977)

(untitled) - Pouradier, J. (J. Chim. Phys., 1964)

(untitled) - Kim, J. S.; Kodagahally, R.; Strekowski, L.; Patonay, G. (Talanta, 2005)

(untitled) - Brömme, T.; Schmitz, C.; Moszner, N.; Burtscher, P.; Strehmel, N.; Strehmel, B. (ChemistrySelect, 2016)

Photopolymerisation Initiating Systems - Schmitz, C.; Oprych, D.; Kutahya, C.; Strehmel, B. (NIR Light for Initiation of Photopolymerization, 2018)

(untitled) - Schmitz, C.; Pang, Y.; Gülz, A.; Gläser, M.; Horst, J.; Jäger, M.; Strehmel, B. (Angew. Chem., Int. Ed., 2019)

Method for automated control of processing parameters - Plümer, L.; Korolik, P.; Koifman, D.; Baumann, H.; Strehmel, B. (2011)

(untitled) - Strehmel, B.; Schmitz, C.; Cremanns, K.; Göttert, J. (Chem. – Eur. J., 2019)

(untitled) - Nguyen, M. T.; Locas, M. A. (Thermally reactive near-infrared absorbing acetal copolymers, methods of preparation and methods of use, 2006)

(untitled) - Roschger, P.; Michaelis, S.; Hassenrueck, K.; Berneth, H.; Callant, P. (Verfahren zur Herstellung von Cyaninfarbstoffen, 1995)

(untitled) - Baumann, H.; Ernst, U.; Goez, M.; Griesbeck, A.; Oelgemöller, M.; Oppenländer, T.; Schlörholz, M.; Strehmel, B. (Nachr. Chem., 2014)

(untitled) - Ignatyev, N. D.; Kucheryna, A. D.; Welz-Biermann, U. D.; Willner, H. P. D. (FAP-Farbstoffe, 2005)

(untitled) - Kavarnos, G. J.; Turro, N. J. (Chem. Rev., 1986)

(untitled) - Aulin, Y. V.; Liu, M.; Piotrowiak, P. (J. Phys. Chem. Lett., 2019)

(untitled) - Dlott, D. D. (J. Lumin., 1990)

(untitled) - Mustroph, H. (ChemPhysChem, 2016)

(untitled) - Mustroph, H.; Ernst, S. (Chem. Unserer Zeit, 2011)

(untitled) - Lee, S.; George Thomas, R.; Ju Moon, M.; Ju Park, H.; Park, I.-K.; Lee, B.-I.; Yeon Jeong, Y. (Sci. Rep., 2017)

(untitled) - Yan, Y.; Chen, J.; Yang, Z.; Zhang, X.; Liu, Z.; Hua, J. (J. Mater. Chem. B, 2018)

(untitled) - Xu, Q.; Shen, Y.; Zhang, Y.; Shao, X. (Bioorg. Med. Chem. Lett., 2019)

(untitled) - Kütahya, C.; Schmitz, C.; Strehmel, V.; Yagci, Y.; Strehmel, B. (Angew. Chem., Int. Ed., 2018)

(untitled) - Uo, M.; Kudo, E.; Okada, A.; Soga, K.; Jogo, Y. (J. Photopolym. Sci. Technol., 2009)

UV Coatings. Basics, Recents Developments and New Applications - Schwalm, R. (Elsevier, 2007)

(untitled) - Romańczyk, P. P.; Kurek, S. S. (Electrochim. Acta, 2017)

(untitled) - Bonardi, A. H.; Dumur, F.; Grant, T. M.; Noirbent, G.; Gigmes, D.; Lessard, B. H.; Fouassier, J.-P.; Lalevée, J. (Macromolecules, 2018)

(untitled) - Bonardi, A.-H.; Bonardi, F.; Morlet-Savary, F.; Dietlin, C.; Noirbent, G.; Grant, T. M.; Fouassier, J.-P.; Dumur, F.; Lessard, B. H.; Gigmes, D.; Lalevée, J. (Macromolecules, 2018)

(untitled) - Bonardi, A.; Bonardi, F.; Noirbent, G.; Dumur, F.; Dietlin, C.; Gigmes, D.; Fouassier, J.-P.; Lalevée, J. (Polym. Chem., 2019)

(untitled) - Bonardi, A. H.; Bonardi, F.; Dumur, F.; Gigmes, D.; Fouassier, J. P.; Lalevée, J. (Macromol. Rapid Commun., 2019)

(untitled) - Samanta, A.; Vendrell, M.; Das, R.; Chang, Y.-T. (Chem. Commun., 2010)

(untitled) - Gorka, A. P.; Nani, R. R.; Zhu, J.; Mackem, S.; Schnermann, M. J. (J. Am. Chem. Soc., 2014)

Principles of Polymerization - Odian, G. (John Wiley & Sons, 2004)

(untitled) - Weyts, K. F.; Goethals, E. J. (Polym. Bull., 1988)

(untitled) - Goethals, E. J.; Van de Velde, M.; Eckhaut, G.; Bouquet, G. (ACS Symp. Ser., 1985)

(untitled) - Goethals, E. J.; Vlegels, M. A. (Polym. Bull., 1981)

(untitled) - Goethals, E. J.; Schacht, E. H.; Bruggeman, P.; Bossaer, P. (ACS Symp. Ser., 1977)

(untitled) - Iwai, Y.; Kunita, K. (Compound having polymethine-chain structure, image forming material, planographic printing plate precursor, and image forming method using the same, method of making planographic printing plate, and planographic printing method, 2007)

(untitled) - Iwai, Y.; Kunita, K. (Compound having polymethine-chain structure, image forming material, planographic printing plate precursor, and image forming method using the same, method of making planographic printing plate, and planographic printing method, 2006)

(untitled) - Simpson, P.; Baumann, H.; Strehmel, B. (Sensitizer/initiator combination for negative-working thermal-sensitive compositions usable for lithographic plates, 2009)

(untitled) - Kropp, M. A.; Baillargeon, M.; Park, K. M.; Bhamidapaty, K.; Schuster, G. B. (J. Am. Chem. Soc., 1991)

(untitled) - Schuster, G. B. (Pure Appl. Chem., 1990)

(untitled) - Chatterjee, S.; Davis, P. D.; Gottschalk, P.; Kurz, M. E.; Sauerwein, B.; Yang, X.; Schuster, G. B. (J. Am. Chem. Soc., 1990)

(untitled) - Kabatc, J.; Zasada, M.; Paczkowski, J. (J. Polym. Sci., Part A: Polym. Chem., 2007)

(untitled) - Bruder, F.-K.; Fäcke, T.; Rölle, T. (Polymers (Basel, Switz.), 2017)

(untitled) - Bruder, F.-K.; Hagen, R.; Rölle, T.; Weiser, M.-S.; Fäcke, T. (Angew. Chem., 2011)

(untitled) - Bruder, F.-K.; Deuber, F.; Facke, T.; Hagen, R.; Honel, D.; Jurberg, D.; Kogure, M.; Rolle, T.; Weiser, M.-S. (J. Photopolym. Sci. Technol., 2009)

(untitled) - Sarker, A. M.; Kaneko, Y.; Neckers, D. C. (J. Photochem. Photobiol., A, 1999)

(untitled) - Kaneko, Y.; Sarker, A. M.; Neckers, D. C. (Chem. Mater., 1999)

(untitled) - Sarker, A. M.; Lungu, A.; Mejiritski, A.; Kaneko, Y.; Neckers, D. C. (J. Chem. Soc., Perkin Trans. 2, 1998)

(untitled) - Sarker, A. M.; Kaneko, Y.; Nikolaitchik, A. V.; Neckers, D. C. (J. Phys. Chem. A, 1998)

(untitled) - Popielarz, R.; Sarker, A. M.; Neckers, D. C. (Macromolecules, 1998)

(untitled) - Feng, K.; Zang, H.; Martin, D.; Marino, T. L.; Neckers, D. C. (J. Polym. Sci., Part A: Polym. Chem., 1998)

(untitled) - Sarker, A. M.; Lungu, A.; Neckers, D. C. (Macromolecules, 1996)

(untitled) - Hassoon, S.; Sarker, A.; Polykarpov, A. Y.; Rodgers, M. A. J.; Neckers, D. C. (J. Phys. Chem., 1996)

(untitled) - Hauck, G.; Savariar-Hauck, C.; Timpe, H.-J. (Kodak Polychrome Graphics, 2000)

(untitled) - Berdzinski, S.; Strehmel, B.; Strehmel, V. (Photochem. Photobiol. Sci., 2015)

(untitled) - Strekowski, L.; Lee, H.; Mason, J. C.; Say, M.; Patonay, G. (J. Heterocycl. Chem., 2009)

Handbook of Radical Polymerization - Matyjaszewski, K.; Davis, T. P. (John Wiley & Sons, Inc., 2002)

(untitled) - Jiang, J.; Ye, G.; Wang, Z.; Lu, Y.; Chen, J.; Matyjaszewski, K. (Angew. Chem., Int. Ed., 2018)

(untitled) - McKenzie, T. G.; Fu, Q.; Uchiyama, M.; Satoh, K.; Xu, J.; Boyer, C.; Kamigaito, M.; Qiao, G. G. (Adv. Sci., 2016)

(untitled) - Shanmugam, S.; Xu, J.; Boyer, C. (Angew. Chem., 2016)

(untitled) - Matyjaszewski, K. (Macromolecules, 2012)

(untitled) - Ribelli, T. G.; Fantin, M.; Daran, J.-C.; Augustine, K. F.; Poli, R.; Matyjaszewski, K. (J. Am. Chem. Soc., 2018)

(untitled) - Enciso, A. E.; Fu, L.; Russell, A. J.; Matyjaszewski, K. (Angew. Chem., Int. Ed., 2018)

(untitled) - Yang, Y.; Liu, X.; Ye, G.; Zhu, S.; Wang, Z.; Huo, X.; Matyjaszewski, K.; Lu, Y.; Chen, J. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Matyjaszewski, K. (Chem. Int., 2017)

(untitled) - Ribelli, T. G.; Konkolewicz, D.; Pan, X.; Matyjaszewski, K. (Macromolecules, 2014)

(untitled) - Ribelli, T. G.; Konkolewicz, D.; Bernhard, S.; Matyjaszewski, K. (J. Am. Chem. Soc., 2014)

(untitled) - Dadashi-Silab, S.; Doran, S.; Yagci, Y. (Chem. Rev., 2016)

(untitled) - Tasdelen, M. A.; Uygun, M.; Yagci, Y. (Macromol. Rapid Commun., 2011)

(untitled) - Tasdelen, M. A.; Uygun, M.; Yagci, Y. (Macromol. Chem. Phys., 2010)

(untitled) - Treat, N. J.; Sprafke, H.; Kramer, J. W.; Clark, P. G.; Barton, B. E.; Read de Alaniz, J.; Fors, B. P.; Hawker, C. J. (J. Am. Chem. Soc., 2014)

(untitled) - Pan, X.; Fang, C.; Fantin, M.; Malhotra, N.; So, W. Y.; Peteanu, L. A.; Isse, A. A.; Gennaro, A.; Liu, P.; Matyjaszewski, K. (J. Am. Chem. Soc., 2016)

(untitled) - Kutahya, C.; Allushi, A.; Isci, R.; Kreutzer, J.; Ozturk, T.; Yilmaz, G.; Yagci, Y. (Macromolecules, 2017)

(untitled) - Aydogan, C.; Kutahya, C.; Allushi, A.; Yilmaz, G.; Yagci, Y. (Polym. Chem., 2017)

(untitled) - Kutahya, C.; Aykac, F. S.; Yilmaz, G.; Yagci, Y. (Polym. Chem., 2016)

(untitled) - Jockusch, S.; Yagci, Y. (Polym. Chem., 2016)

(untitled) - Stenzel, M. H.; Barner-Kowollik, C. (Mater. Horiz., 2016)

(untitled) - Zwikker, J. L. (Pharm. Weekbl., 1933)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Wu, P.; Feldman, A. K.; Nugent, A. K.; Hawker, C. J.; Scheel, A.; Voit, B.; Pyun, J.; Fréchet, J. M. J.; Sharpless, K. B.; Fokin, V. V. (Angew. Chem., Int. Ed., 2004)

(untitled) - Tasdelen, M. A.; Yagci, Y. (Angew. Chem., Int. Ed., 2013)

(untitled) - Gacal, B.; Akat, H.; Balta, D. K.; Arsu, N.; Yagci, Y. (Macromolecules, 2008)

(untitled) - Tasdelen, M. A.; Yilmaz, G.; Iskin, B.; Yagci, Y. (Macromolecules, 2012)

(untitled) - Temel, G.; Aydogan, B.; Arsu, N.; Yagci, Y. (Macromolecules, 2009)

(untitled) - Kütahya, C.; Yagci, Y.; Strehmel, B. (ChemPhotoChem, 2019)

(untitled) - Lelièvre, T.; Stoltz, G. (Acta Numerica, 2016)

(untitled) - Li, L.; Baker, T. E.; White, S. R.; Burke, K. (Phys. Rev. B, 2016)

(untitled) - Grajciar, L.; Heard, C. J.; Bondarenko, A. A.; Polynski, M. V.; Meeprasert, J.; Pidko, E. A.; Nachtigall, P. (Chem. Soc. Rev., 2018)

(untitled) - Rupp, M. (Int. J. Quantum Chem., 2015)
Special issue on machine learnin and quantum mechanics.

(untitled) - Grisafi, A.; Fabrizio, A.; Meyer, B.; Wilkins, D. M.; Corminboeuf, C.; Ceriotti, M. (ACS Cent. Sci., 2019)

(untitled) - Cremanns, K.; Roos, D. (arXiv, 2017)
https://arxiv.org/abs/1710.06202v2 (16 November 2019).

(untitled) - Cremanns, K.; Schmitz, C.; Wagner, L. (Farbe und Lack, 2019)